Evaluation of gingival melanin depigmentation by using Er:YAG laser: ex-vivo and clinical studies - Stas, Yasser Tharwat (2018)
Gingiva hyperpigmentation is more often a non-pathological problem, but clinically it is considered unaesthetic especially in cases of excessive gingival display during smiling. Many treatment methods are available to solve the problem such as chemical peeling, surgery and laser ablation. The laser by its various wavelengths is considered a standard treatment in gingival depigmentation. Er: YAG laser is one of the most studied laser in soft tissues and hard tissues management. In this study, different power settings of the same wavelength of Er: YAG laser were compared between each other and the favorable of them were chosen for gingival depigmentation. The study was conducted in two phases beginning with ex-vivo animal tissue experiment followed by prospective human experiment phase. In the animal phase, 24 different power settings were applied in the hyperpigmented gingiva mucosa of a recently slaughtered sheep’s head. Altered zone, carbonization, speed and operator controllability parameters were examined for the purpose of choosing 4 best power settings to be applied to the human study. 2J/cm2 and 4J/cm2 fluences and SP and VLP pulse durations were chosen for the human study. In the human study, a total of 40 adult female and nonsmoker patients were recruited and were divided randomly into four groups of 10 patients each (2J/cm2VLP, 2J/cm2SP, 4J/cm2VLP and 4J/cm2SP). One power setting was applied to each group. Clinical and biological evaluation was performed. Pain, bleeding, satisfaction, carbonization, speed of removal and histological investigation parameters were tested. Ablated tissue specimen was sent for histological analysis. The four power settings proved safety, patient satisfaction and dentist controllability, and efficiency in the removal of the pigmentations. There was no statistical difference between them regarding histology, pain, satisfaction and bleeding (P>0.05). There was significant difference between groups regarding ablation time (P<0.05). Histological analysis showed a very shallow damage in the lamina propria with a depth of 10 to 60 microns. In conclusion, fluence of 2J/cm2 and 4J/cm2 with pulse duration of SP (0.3ms) and VLP (1ms) for each fluence were found to be safe, effective and efficient. Fluence <2J/cm2 might not be effective due to increase carbonization of the superficial gingiva of the lased areas, thus obscuring the vision of the operator, and fluence >5J/cm2 is uncontrollable. Peak power is less critical than the dose in aspect of ablation time. Based on ex-vivo animal study and clinical trial, examining the technical, clinical and biological aspects using Er: YAG laser in this study. The final optimum power settings obtained are: 2J/cm2 VLP which is optimum for the beginner practitioner and 4J/cm2SP which is optimum for the experienced practitioner.